Tinjauan Lingkungan Fisik Pada Madrasah Aliyah Al Muslim Ambon - Safna Kaplale; Vera Paulin Kay; Kalsum Lussy; Simson Melmambessy (Jurnal Administrasi Terapan, 2024)
The purpose of this writing is to be able to find out how the adequate physical work environment in "Madrasah Aliyah Al-Muslim Ambon".This research is qualitative in which the author describes the physical work environment at Madrasah Aliyah Al-Muslim Ambon. The data analysis technique used in this writing is with a qualitative analysis technique, namely using a theoretical approach according to experts related to this writing. The results of this study show that the physical environment in Madrasah Aliyah Al-Muslim Ambon is not yet feasible.The conclusion that can be drawn from this writing is that the physical condition that occurs at Madrasah Aliyah Al-Muslim Ambon is seen from the color of the paint on the walls that have begun to fade and be damaged due to the condition of the building, poor lighting due to the absence of window installation so that the sun's rays reflect the light directly, the air in the room due to the absence of ceiling installation in each room which can cause the air temperature to increase further and leakage on zinc roofs, the humidity on the walls is the same as the color of the paint that has faded and is damaged due to the condition of the building that has been damp, and the cleanliness of the room has not been properly maintained due to the floor that has been damaged because it is still using basic cement. Keywords :Physical Environment